Relating basic properties of bright early-type dwarf galaxies to their location in Abell 901/902 - Barazza, F; Wolf, C; Gray, M; Jogee, S; Balogh, M; McIntosh, D; Bacon, D; Barden, M; Bell, E; Boehm, A; Caldwell, J; Haeussler, B; et al. (2009)
We present a study of the population of bright early-type dwarf galaxies in the multiple-cluster system Abell 901/902. We use data from the STAGES survey and COMBO-17 to investigate the relation between the color and structural properties of the dwarfs and their location in the cluster. The definition of the dwarf sample is based on the central surface brightness and includes galaxies in the luminosity range -16 >= M_B >~-19 mag. Using a fit to the color magnitude relation of the dwarfs, our sample is divided into a red and blue subsample. We find a color-density relation in the projected radial distribution of the dwarf sample: at the same luminosity dwarfs with redder colors are located closer to the cluster centers than their bluer counterparts. Furthermore, the redder dwarfs are on average more compact and rounder than the bluer dwarfs. These findings are consistent with theoretical expectations assuming that bright early-type dwarfs are the remnants of transformed late-type disk galaxies involving processes such as ram pressure stripping and galaxy harassment. This indicates that a considerable fraction of dwarf elliptical galaxies in clusters are the results of transformation processes related to interactions with their host cluster.